Mutual regulation of plant phospholipase D and the actin cytoskeleton - Pleskot, Roman; Potocký, Martin; Pejchar, Premysl; Linek, Jan; Bezvoda, Radek; Martinec, Jan; Valentová, Olga; Novotná, Zuzana; Zárský, Viktor (The Plant journal, 2010)
Membrane lipids and cytoskeleton dynamics are intimately inter-connected in the eukaryotic cell; however, only recently have the molecular mechanisms operating at this interface in plant cells been addressed experimentally. Phospholipase D (PLD) and its product phosphatidic acid (PA) were discovered to be important regulators in the membrane-cytoskeleton interface in eukaryotes. Here we report the mechanistic details of plant PLD-actin interactions. Inhibition of PLD by n-butanol compromises pollen tube actin, and PA rescues the detrimental effect of n-butanol on F-actin, showing clearly the importance of the PLD-PA interaction for pollen tube F-actin dynamics. From various candidate tobacco PLDs isoforms, we identified NtPLDbeta1 as a regulatory partner of actin, by both activity and in vitro interaction assays. Similarly to published data, the activity of tobacco PIP(2)-dependent PLD (PLDbeta) is specifically enhanced by F-actin and inhibited by G-actin. We then identified the NtPLDbeta1 domain responsible for actin interactions. Using sequence- and structure-based analysis, together with site-directed mutagenesis, we identified Asn323 and Thr382 of NtPLDbeta1 as the crucial amino acids in the actin-interacting fold. The effect of antisense-mediated suppression of NtPLDbeta1 or NtPLDdelta on pollen tube F-actin dynamics shows that NtPLDbeta1 is the active partner in PLD-actin interplay. The positive feedback loop created by activation of PLDbeta by F-actin and of F-actin by PA provides an important mechanism to locally increase membrane-F-actin dynamics in the cortex of plant cells.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Actins; Gene Expression Regulation, Plant; Cytoskeleton; aktiny; Mutagenesis, Site-Directed; cytoskelet; Cloning, Molecular; Gene Knockdown Techniques; fosfolipasa D; mutageneze cílená; Isoenzymes; tabák; Amino Acid Sequence; Pollen Tube; izoenzymy; regulace genové exprese u rostlin; Phospholipase D; genový knockdown; klonování DNA; molekulární sekvence - údaje; Sequence Analysis, Protein; pylová láčka; Nicotiana; sekvenční analýza proteinů